Modeling and Optimization of Fresh Properties of Kenaf Biofibrous Concrete Using Response Surface Methodology - Ogunbode Ezekiel Babatunde; Moses Daniel Walbe; Adamu Bala; Mohoro Ibrahim Sarki; Lawal Temitope Adesina (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
The pursuit of sustainable construction materials has led to growing interest in biofibrous concrete reinforced with natural fibres. This study investigates the influence of kenaf fibre length and volume fraction on the fresh properties of concrete—slump, compacting factor, and Vebe time—using Response Surface Methodology (RSM). A face-centred Central Composite Design (CCD) was employed to model and optimize the mix design. Experimental results revealed that, increasing fibre length and content significantly reduced workability, with slump decreasing from 90 mm to 5 mm as fibre volume increased from 0.5% to 1.5% and length from 25 mm to 75 mm. Regression models demonstrated strong predictive accuracy (R² > 90%) across all responses. Multi-response optimization using desirability function identified the ideal mix as 36.87 mm fibre length and 0.78% volume fraction, yielding a predicted slump of 49.99 mm, compacting factor of 0.90, and Vebe time of 18.23s. Laboratory validation produced close agreement, with prediction errors below 8%. These findings affirm the potential of kenaf fibres in sustainable concrete applications and align with earlier findings on natural fibre concrete systems, reinforcing the robustness of RSM in mix design optimization.